PERSEPSI PELAJAR TERHADAP VIDEO CONFERENCE SAAT PANDEMI COVID-19 - Ajeng Harya Artanti; Hasan Subekti (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research has the aims of representing science learning with the help of video conferencing during the Covid-19 pandemic era, which includes aspects of the level of productivity or pedagogy of science teachers as facilitators and active involvement interests, as well as the expectations of learners. This research method used an exploratory study research type with quantitative and qualitative approaches. Data collection techniques using survey techniques that use instruments questionnaire where scale 5 Likert and open. The technique of determining participants using purposive sampling. There are two data analyses of Miles and Huberman’s data analysis and quantitative descriptive analysis techniques through percentage calculations. The results of the research showed their perception preference for video conference media is very helpful for them in learning online and fostering the interest of learners. Then in the pedagogy aspect, the teacher gives a clear explanation of the material, but the use of video conference has not been fully effective due to connection quality problems which ultimately cut learning time and interaction such as feedback and discussions are only given if there is time left in learning. The expectations of learners include learning by being directly like practice, demonstrating by utilizing props as well as improving the quality of visual video, images and sound in the use of video conferences. The implications of this research include the use of video conference is very helpful for learners’ communication in online learning and tends to develop the interest of learners.